Outcome of Ovarian Electrocoagulation in Anovulatory Patients - Rosa W.Guillermo ; Anwandter S. Carlos (Academic Journal of Clinicians, 2024)
Eighteen anovulatory patients refractory to the use of Clomiphene Citrate (CC) underwent ovarian electrocoagulation during a laparoscopy performed as part of the study of their infertility. Fourteen patients (78%) ovulated spontaneously or with CHD and 10 (56%) became pregnant, 7 of them with CHD. Three patients (21%) had a first trimester spontaneous abortion and one patient (5.6%) presented ovarian failure after surgery. It is concluded that in anovulatory patients refractory to CC, ovarian electrocoagulation can be performed during the diagnostic laparoscopy that is part of the study of infertile women.